A probabilistic map of Costa Rican peatlands based on vegetation, ecosystem, and soil inventories - Emily Rabel; Julie Loisel; Alex Barthelmes; Cristina Malpica-Piñeros; Cosima Tegetmeyer; Jacklyn Rivera Wong; Laura Villegas-Mejia (Scientific Reports)
Abstract This article presents the first published peatland map for Costa Rica. A probabilistic approach using vegetation, ecosystem, and soil datasets was used to predict the distribution and extent of peatlands found below 700 m in elevation. High-elevation sites found in the Talamanca Mountains were manually identified using satellite imagery; those peatlands are small in size (< 0.05 km2). Our analysis produced an estimated low-elevation peatland extent of 1433 km2 and a high-elevation peatland extent of 23.08 km2, yielding an estimated total extent of 1456 km2 for Costa Rica. This figure falls close to the middle of previously published extent estimates for this country, which vary widely (577–2670 km2). An agreement analysis between previously published maps and this new product is also presented. Plotting the peatland area of Costa Rica in a climate space (mean annual precipitation vs. precipitation seasonality) highlights key climatic differences between our peatland types/regions, hinting at broad-scale effects of climate-landscape interactions. As for the probability map therein, we stress that its accuracy is limited by data availability and quality, as well as ground-referencing information. Still, the new product can provide guidance for land management, policymaking, and future science endeavors.